Sosialisasi Technopreneurship Produktif Dan Kreatif Pada Masyarakat Masbagik Utara Baru - Dedy Febry Rachman; Syaiful Amri (Valid Jurnal Pengabdian, 2026)
The development of information and communication technology in the digital era presents both opportunities and significant challenges for village-level economies. Masbagik Utara Baru Village in East Lombok Regency possesses promising potential for local Micro, Small, and Medium Enterprises (MSMEs); however, the utilisation of digital technology for operational development and business marketing remains relatively limited. This community service initiative—conducted through a session on "Productive and Creative Technopreneurship"—aims to enhance the understanding, motivation, and practical skills of residents and business owners regarding the adoption of digital technology. The implementation process comprised three stages: (1) preparation and needs analysis; (2) execution, involving material presentations, interactive workshops, and simulations of digital marketing and app-based financial record-keeping; and (3) impact evaluation. The results indicate an 85% increase in participants' understanding of technopreneurship concepts, the creation of promotional content, and the optimisation of social media and e-commerce platforms. The initiative fostered a collective awareness regarding the transition from traditional business models to productive, creative, and sustainable technology-based entrepreneurship.